Hierarchically structured electrospinning nanofibers for catalysis and energy storage. (June 2019) - Li, Shuai; Cui, Zhimin; Li, Dianming; Yue, Guichu; Liu, Jing; Ding, Hongge; Gao, Songwei; Zhao, Yuchao; Wang, Nü; Zhao, Yong
Abstract: Hierarchically structured nanomaterials are critical for the catalysis and energy storage to make full use of the surfaces and space to elevate activities. Electrospinning is a very convenient technique for programmable fabrication of different kinds of nanofibers with diverse compositions as well as complex internal and external structures for various demands in application of catalysis and energy storage fields. In this review, some effective electrospinning strategies for constructing various nanofibrous materials with multilevel structures are presented. Firstly, hierarchically hollow structured nanofibers are described and categorized including hollow fibers, wire-in-tube fibers, tube-in-tube fibers, peapod-like fibers, multichannel fibers and outer branched fibers etc. The unique properties arose from the special hierarchical structures effect such as multiple heterogeneous interfaces, confined space and large specific area are discussed and some representative applications in catalysis and energy storage are presented. Finally, the challenges and perspectives of future researches on the electrospinning hierarchically structured nanofibers for various applications are highlighted. Highlights: We summarized multilevel structure from a new perspective based on the configuration of the nanofibers. This review systematacially summarized the methods to prepare hierarchically structured nanofibers. The key role of hierarchical structure in the application of catalytic and energy fields was elaborated.